DOP14 Ultra-high magnification endocytoscopy and molecular markers for defining endoscopic and histologic remission in Ulcerative Colitis. (27th May 2021) - Iacucci, M; Nardone, O M; Jeffery, L; Acharjee, A; Zardo, D; Smith, S C; Bazarova, A; Cannatelli, R; Shivaji, U N; Williams, J; Georgios, G; Ghosh, S
Abstract: Background: Endoscopic and histological remission are important goals to achieve in patients with ulcerative colitis (UC). We aimed to define deep remission by assessing cellular architecture, expression of molecular markers and their correlation with endoscopic scores by using ultra-high-magnification endocytoscopy and histological indices Methods: We conducted a prospective study enrolling 29 UC patients (18 males, mean age 41y) referred at a tertiary academic centre for assessing endoscopic remission (ER). All patients underwent colonoscopies with 520-fold magnification endocytoscope. The inflammatory activity was scored using the Mayo Endoscopic Score (MES). ER was defined as MES 0. To assess the grade of inflammation using ECS we set an ECS score (ECSS), whose parameters were summarized in table 1. Biopsies were taken targeting either the worst affected area of inflammation or the most representive area of ER and scored according to Nancy Histopatological Index (NHI) and Robarts Histopatological Index (RHI). Histological remission (HR) is defined as NHI≤1, and RHI≤3 without neutrophils in the epithelium and lamina propria.The correlation between ECSS and MES and with histological scores were determined. Soluble analytes relevant to inflammation were measured in serum and mucosal culture supernatants using Procartaplex Luminex assays and studied by Partial Least Square Discriminant Analysis (PLS-DA) and logistic model. Mucosal RNA sequencing and gene enrichment analysis (GO, KEGG) were performed to define differentially expressed genes/pathways. Results: ECSS correlated strongly with RHI (r=0.89 [95%CI 0.51–0.98] and NHI (r=0.86 [95%CI 0.42–0.98] but poorly with MES (r=0.28 [95%CI-0.27–0.70]). We identified that BDNF, MIP-1α and sVCAM-1 predicted HR. Mucosal biopsy cultures also identified sVCAM-1 associated with healed mucosa. RNA-seq analysis identified genes expressed in colonic biopsies that discriminated between healed and non-healed mucosa and overlapped gene expression shared between ECSS, RHI or NHI defined healing. Based on PLS-DA, for healing vs. non healing comparison as defined by RHI, Nancy, Mayo and ECCS we found 32, 83, 127 and 60 differentially genes respectively. These included genes relevant to TGF-b signaling, macrophage recruitment into tissues, neutrophil and plasma cell function and tumour suppressor genes (Fig.1) A number of those identified were shared by MES and ECSS defined healing as well as histological criteria defined healing. Conclusion: ECS may sit between endoscopy and histology but closer to the latter and identifies gene expression markers and pathways that are also detected by histology. *OMN, LJ, AA equal authors